2008
DOI: 10.1021/jp077594d
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Water Adsorption onto a Calcite Surface as a Function of Relative Humidity

Abstract: We have developed a molecular dynamics scheme in order to understand the dynamics of water adsorption on calcite surfaces as a function of relative humidity. In contrast to previous studies where either a monolayer or bulk water was assumed to cover the surface, we observe the formation of two to three prominent layers of water depending on the relative humidity. Due to the fact that these simulations are at room temperature, the distribution of water molecules on the surface is inhomogeneous and nonuniform. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
70
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(86 citation statements)
references
References 37 publications
15
70
0
1
Order By: Relevance
“…Table 4 gives the summary of the water adsorption calorimetric data. The computed hydration energy value reported from various atomistic simulation techniques range between À79.2 to À138.9 kJ/mol (Liang et al, 1996;de Leeuw and Parker, 1998;Kerisit and Parker, 2004;Rahaman et al, 2008). The enthalpy of water adsorption determined from the water adsorption calorimetric measurements (À96.26 ± 0.96 kJ/mol) falls within the theoretically calculated range.…”
Section: Water Adsorption Experimentsmentioning
confidence: 53%
See 1 more Smart Citation
“…Table 4 gives the summary of the water adsorption calorimetric data. The computed hydration energy value reported from various atomistic simulation techniques range between À79.2 to À138.9 kJ/mol (Liang et al, 1996;de Leeuw and Parker, 1998;Kerisit and Parker, 2004;Rahaman et al, 2008). The enthalpy of water adsorption determined from the water adsorption calorimetric measurements (À96.26 ± 0.96 kJ/mol) falls within the theoretically calculated range.…”
Section: Water Adsorption Experimentsmentioning
confidence: 53%
“…6) could possibly be due to distinct modes of water adsorption on different active sites on nanocalcite surface. Several molecular dynamic simulation studies on adsorbed water density distribution on calcite surface (Kerisit and Parker, 2004;Rahaman et al, 2008) have also indicated the existence of three different conformational modes for water adsorption on calcite surface. The two modes within the first layer have two hydrogen atoms of the water molecule pointing either up away from the surface or down toward a carbonate ion.…”
Section: Water Adsorption Experimentsmentioning
confidence: 99%
“…In the case of metal oxides (CaO, MgO, and Fe 2 O 3 ) and carbonates (CaCO 3 and MgCO 3 ), dissociation of water molecules at the interfaces is energetically favorable because hydroxylated surfaces are more stable than metal-terminated surfaces under ambient conditions (15,41,42). Recent experiments and molecular dynamic simulations have shown the free energy of adsorption of water on calcite surfaces (43,44) to be as low as −10.6 kcal mol −1 .…”
Section: Discussionmentioning
confidence: 99%
“…Some previous studies by Chenevert (1970a,b), Kahr and Madsen (1995) have reported the effect of clay minerals on water adsorption capacity on reservoir rocks. Kerisit and Parker (2004), Rahaman et al (2008) and Schultz et al (2013) proposed that calcite is characterized by high surface area and weak affinity for water. Consequently, shale rocks with calcite will have a relatively low water capacity in the shale samples.…”
Section: W Shen Et Almentioning
confidence: 99%